Development of a Digital Assessment Model for Evaluating Early Childhood Emotional Readiness for Elementary School Entry - Asjadul Khoiriyah; Nenny Mahyuddin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aimed to develop a Digital Assessment Model for evaluating early childhood emotional readiness before primary school entry. The model was designed to assess five dimensions of emotional readiness, namely self-awareness, self-regulation, self-control, self-confidence, and self-esteem, while providing teachers with a systematic, efficient, and technology-supported assessment tool. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The developed model can be applied in early childhood education institutions, kindergarten settings, school readiness assessment programs, educational technology development, and child development monitoring. It can support teachers, school administrators, educational researchers, and policymakers in conducting systematic and efficient emotional readiness assessments before children transition to primary school. A practical technological solution that enhances assessment efficiency, improves documentation quality, and supports educational decision-making in early childhood education.